The politics and governance of research into solar geoengineering. (14th March 2021) - McLaren, Duncan; Corry, Olaf
Abstract: Research into solar geoengineering, far from being societally neutral, is already highly intertwined with its emerging politics. This review outlines ways in which research conditions or constructs solar geoengineering in diverse ways, including the forms of possible material technologies of solar geoengineering; the criteria and targets for their assessment; the scenarios in which they might be deployed; the publics which may support or oppose them; their political implications for other climate responses, and the international relations, governance mechanisms, and configurations of power that are presumed in order to regulate them. The review also examines proposals for governance of research, including suggested frameworks, principles, procedures, and institutions. It critically assesses these proposals, revealing their limitations given the context of the conditioning effects of current research. The review particularly highlights problems of the reproduction of Northern norms, instrumental approaches to public engagement, a weak embrace of precaution, and a persistent—but questionable—separation of research from deployment. It details complexities inherent in effective research governance which contribute to making the pursuit of solar geoengineering risky, controversial, and ethically contentious. In conclusion, it suggests a case for an explicit, reflexive research governance regime developed with international participation. It suggests that such a regime should encompass modeling and social science, as well as field experimentation, and must address not only technical and environmental, but also the emergent social and political, implications of research. This article is categorized under: Social Status of Climate Change Knowledge > Knowledge and Practice Policy and Governance > Multilevel and Transnational Climate Change Governance Abstract : Extant proposals for governance of solar geoengineering research (red boxes) fail to encompass critical emergent social and political implications (blue boxes). Explicit, international, reflexive governance covering all forms of research (from modeling to experiments) is urgently needed.